Age- and Sex-Specific Prevalence and Modifiable Risk Factors of Mild Cognitive Impairment Among Older Adults in China: A Population-Based Observational Study - Fu, Jingzhu; Liu, Qian; Du, Yue; Zhu, Yun; Sun, Changqing; Lin, Hongyan; Jin, Mengdi; Ma, Fei; Li, Wen; Liu, Huan; Zhang, Xumei; Chen, Yongjie; et al. (Frontiers in Aging Neuroscience, 2020)
Background: There are minimal data available on the prevalence of mild cognitive impairment (MCI) in Chinese older adults, and the existing information on MCI shows important geographical variations. Objective: We aimed to assess the prevalence and risk factors for MCI by age and sex among older adults in a North Chinese population. Methods: In this population-based cross-sectional study, we enrolled a random sample of 4,943 adults aged ≥60 years from March 2018 to June 2019 in Tianjin, China. Of these, 312 individuals were excluded due to the lack of curtail information (e.g., fasting blood test). As a result, 4,631 subjects were assessed. Neuropsychological assessments including Mini-Mental State Examination Scale and Activities of Daily Living Scale were applied for the identification of MCI subjects. Results: The mean (SD) age of the 4,631 participants was 67.6 (4.89) years, and 2579 (55.7%) were women. The overall age- and sex-standardized prevalence of MCI in our study population was 10.7%. There were significant associations of MCI with age (65-69 vs. 60-64 years, OR=0.74; 95% confidence interval (CI): 0.58, 0.96), physical activity (PA) (≥23.0 vs. < 23.0 MET- hours/week, OR=0.79; 95% CI: 0.64, 0.96), body mass index (BMI) (OR=0.92; 95% CI: 0.89, 0.95), grip strength (GS) (OR=0.50; 95% CI: 0.38, 0.67), hypertension (yes vs. no, OR=1.44; 95% CI: 1.18, 1.77), sleepy state (OR=1.80; 95% CI: 1.36, 2.37), longer sleep duration (OR=1.40; 95% CI: 1.14, 1.72). The inverse association between BMI and MCI was stronger in older age groups (P for heterogeneity=0.003). Conclusions: The age- and sex-standardized prevalence of MCI was 10.7% in the study area. PA, BMI, GS, sleepy state, sleep duration and hypertension were associated with MCI. Additionally, TG and BMI might have different effects on the presence of MCI at different sex and age stages, respectively.